Odpowiedź:
Założenia po obliczeniach przedstawiono na końcu wyliczeń
a)
a = b/c
ca = b
c = b/a
założenie :
c ≠ 0 ∧ a ≠ 0
b)
S = 1/2at²
2S = at²
t = √(2S/a)
założenie :
a ≠ 0 ∧ 2S/a ≥ 0
c)
(x + a)/b + c = d
x + a + cb = bd
x = bd - cd - a
założenie:
b ≠ 0
d)
y = 3x - 5
3x = y + 5
x = (y + 5)/3
e)
k - P = (x + y)/3
3(k - P) = x + y
x = 3(k - P) - y
f)
(a + x)/b = y
a + x = by
b = (a + x)/y
założenie:
b ≠ 0 ∧ y ≠ 0
g)
a/(2y - b) = c
założenie:
2y - b ≠ 0 ∧ c ≠ 0
2y ≠ b
y ≠ b/2
a = c(2y - b)
a = 2cy - bc
2cy = a + bc
y = (a + bc)/2c
założenie:
2y - b ≠ 0 ∧ c ≠ 0
2y ≠ b
y ≠ b/2
h)
aby + c = d - e
aby = d - c - e
y = (d - c - e)/ab
założenie a ≠ 0 ∧ b ≠ 0
i)
(ax - b)/c = d
ax - b = cd
ax = cd + b
x = (cd + b)/a
założenie :
c ≠ 0 ∧ a ≠ 0
j)
(x + a)b/c = d
b(x + a) = cd
bx + ab = cd
bx = cd - ab
x = (cd - ab)/b
założenie:
c ≠ 0 ∧ b ≠ 0